Aspects of Authentic Spoken German: Awareness and Recognition of Elision in the German Classroom1. Issue 1 (25th May 2016) - Lightfoot, Douglas
Abstract : This work discusses the importance of spoken German in classroom instruction. The paper examines the nature of natural spoken language as opposed to written language. We find a general consensus that the prevailing language measure (whether pertaining to written or spoken language) in instructional settings more often typifies the rules associated with a written variety to the relative exclusion of norms associated with natural spoken language. A discussion of authentic spoken language and pragmatics in the classroom follows. The principle linguistic notion examined is elision (dropping certain sounds), but we also look at assimilation (sounds becoming more alike) due to its high frequency of occurrence with elision . The article then presents suggestions for classroom instruction on awareness and recognition of spoken language, along with the contexts in which spoken language occurs.